Growth and structure of WC/Si multilayer x-ray mirror - Pershyn, Y.P.; Chumak, V.S.; Shypkova, I.G.; Mamon, V.V.; Devizenko, A.Yu.; Kondratenko, V.V.; Reshetnyak, M.V.; Zubarev, E.N. (Вопросы атомной науки и техники, 2018)
WC/Si multilayer X-ray mirrors (MXMs) with nominal layers thicknesses of 0.2…30.3 nm (periods: 0.7…38.9 nm) were deposited by direct current magnetron sputtering and studied by X-ray diffraction and cross-sectional transmission electron microscopy (TEM). Carbide and silicon layers are amorphous throughout the studied thickness range. The WC layers interact with Si layers with formation of tungsten silicides (WSi₂, W₅Si₃) and silicon carbide in as-deposited state. The bottom interlayer (WC-on-Si) consists of two subzones of approximately equal thickness. An estimation of the thickness, density, and composition of all layers is made. Based on the experimental data, a five-layer model of the WC/Si MXM structure is suggested. Методами рентгенівської дифракції та просвічувальної електронної мікроскопії досліджені багатошарові рентгенівські дзеркала (БРД) WC/Si, що виготовлені методом прямоточного магнетронного розпилення з фіксованими швидкостями осадження з номінальними товщинами шарів у діапазоні 0,2…30,3 нм (періоди 0,7…38,9 нм). У всьому діапазоні досліджуваних товщин шари WC та Si являються аморфними. Шари WC та Si взаємодіють з утворенням силіцидів вольфраму (WSi₂, W₅Si₃) та карбіду кремнію в початковому стані. Нижня перемішана зона складається з двох перемішаних підзон приблизно рівної товщини. Зроблена оцінка товщини, щільності та складу всіх шарів. Спираючись на експериментальні результати запропонована п’ятишарова модель будови БРД WC/Si. Методами рентгеновской дифракции и просвечивающей электронной микроскопии исследованы особенности роста многослойных рентгеновских зеркал (МРЗ) WC/Si, изготовленных методом прямоточного магнетронного распыления с номинальными толщинами слоев в диапазоне 0,2…30,3 нм (периоды 0,7…38,9 нм). Во всем диапазоне исследуемых толщин слои WC и Si находятся в аморфном состоянии. Установлено взаимодействие слоев WC и Si с образованием силицидов вольфрама (WSi₂, W₅Si₃) и карбида кремния в исходном состоянии. Нижняя перемешанная зона состоит из двух подзон примерно равной толщины. Сделана оценка толщины, плотности и состава всех слоев. На основе определенных параметров предложена пятислойная модель строения МРЗ WC/Si.